The new Brazil - Roett, Riordan, 1938- (Brookings Institution Press, 2011)
"Recounts Brazil's evolution from remote Portuguese colony, through economic crises that led to more prudent monetary policies, and to its new status as a regional leader, a respected ambassador for the developing world, and an increasingly important partner for the United States and European Union"--Provided by publisher.